Studi Analisis Pengoperasian Cos Phi Generator PLTM Gunung Wugul 2 x 1,5 MW Terhadap Jaringan 20 kV - Arzul Arzul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
PLTM Gunung Wugul is a power plant that utilizes the type of river flow "run of river" which operates with Commercial on Date (COD) on December 3rd, 2021, by PLN Central Java & DIY Distribution Controlling Unit (UP2D). PLTM Gunung Wugul uses a French turbine type with a net head of 68.5m and uses a synchronous generator type with a capacity of 2100 kVA with a cos phi generator capability of 0.8. The generator for the Gunung Wugul PLTM is currently operating with a power factor of 0.95, which PT PLN has asked the PLTM Gunung Wugul to run at a power factor of 0.9. PT PLN assesses that the reactive power production of the PT Indonesia Power plant is still lacking, so a reactive power plant support clause is added with a minimum cos phi 0.9. This results in changes to the operating parameters of the generator. This writing method contains the steps taken by the author in compiling this final project. This writing method is structured to provide clear directions and ways for writers so that the preparation of this thesis can run smoothly. Based on the analysis of operational data for the Gunung Wugul PLTM, the recommended cos phi setting is 0.95. In these conditions, the operating parameters of the unit are in the normal operating conditions and range. Based on the technical specifications of the equipment, the PLTM Gunung Wugul can be operate with a cos phi setting of 0.9. However, these conditions must also see the operating parameters, apart from that the network voltage condition on the MRA03 is currently stable at 20 kV, with operation at cos phi 0.9 it will make the network voltage very high at MRA03-337, with a maximum voltage of 21 kV